Phase‐contrast velocity mapping for highly diffusive fluids: Optimal bipolar gradient pulse parameters for hyperpolarized helium‐3. Issue 4 (11th November 2013) - Martin, Lionel; Maître, Xavier; de Rochefort, Ludovic; Sarracanie, Mathieu; Friese, Marlies; Hagot, Pascal; Durand, Emmanuel
<x xml:space="preserve">Abstract</x> Purpose In MR‐velocity phase‐contrast measurements, increasing the encoding bipolar gradient, i.e., decreasing the field of speed, usually improves measurement precision. However, in gases, fast diffusion during the bipolar gradient pulses may dramatically decrease the signal‐to‐noise ratio, thus degrading measurement precision. These two effects are contradictory. This work aims at determining the optimal sequence parameters to improve the velocity measurement precision. Theory and Methods This work presents the theoretical optimization of bipolar gradient parameters (duration and amplitude) to improve velocity measurement precision. An analytical approximation is given as well as a numerical optimization. It is shown that the solution depends on the diffusion coefficient and T2*. Experimental validation using hyperpolarized 3He diluted in various buffer gases (4He, N2, and SF6) is presented at 1.5 Tesla (T) in a straight pipe. Results Excellent agreement was found with the theoretical results for prediction of optimal field of speed and good agreement was found for the precision in measured velocity, but for SF6 buffered gas. Conclusion The theoretical predictions were validated, providing a way to optimize velocity mapping in gases. Magn Reson Med 72:1072–1078, 2014. © 2013 Wiley Periodicals, Inc.